2021
DOI: 10.1017/s0142716421000102
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical performance in children with dyslexia: the contributions of individual differences in phonological memory and statistical learning

Abstract: Several studies have signaled grammatical difficulties in individuals with developmental dyslexia. These difficulties may stem from a phonological deficit, but may alternatively be explained through a domain-general deficit in statistical learning. This study investigates grammar in children with and without dyslexia, and whether phonological memory and/or statistical learning ability contribute to individual differences in grammatical performance. We administered the CELF “word structure” and “recalling sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 116 publications
(172 reference statements)
0
7
0
Order By: Relevance
“…An inspection of Table 1 reveals that of the 26 separate tasks involving children with dyslexia (across 14 studies), only six showed impairment in statistical learning (He and Tong, 2017;Schiff et al, 2017a;Singh et al, 2018;Tong et al, 2019;Vandermosten et al, 2019;Hedenius et al, 2020), whereas the other 20 reported intact learning van den Broeck, 2015, 2017;Schiff et al, 2017a;Inácio et al, 2018; van der Kleij et al, 2018;van Witteloostuijn et al, 2019van Witteloostuijn et al, , 2021aVandermosten et al, 2019;West et al, 2019). Interestingly, a majority of the studies with children were administered to native speakers of Dutch van den Broeck, 2015, 2017;van der Kleij et al, 2018;Vandermosten et al, 2019;van Witteloostuijn et al, 2019van Witteloostuijn et al, , 2021a, of which all showed evidence of intact learning, except for performance on one of the tasks by Vandermosten et al (2019). Besides Dutch and English (Singh et al, 2018;West et al, 2019), tasks were also administered to native speakers in other languages, such as Cantonese (He and Tong, 2017;Tong et al, 2019), Hebrew (Schiff et al, 2017a), Portuguese (Inácio et al, 2018) and Swedish (Hedenius et al, 2020).…”
Section: Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…An inspection of Table 1 reveals that of the 26 separate tasks involving children with dyslexia (across 14 studies), only six showed impairment in statistical learning (He and Tong, 2017;Schiff et al, 2017a;Singh et al, 2018;Tong et al, 2019;Vandermosten et al, 2019;Hedenius et al, 2020), whereas the other 20 reported intact learning van den Broeck, 2015, 2017;Schiff et al, 2017a;Inácio et al, 2018; van der Kleij et al, 2018;van Witteloostuijn et al, 2019van Witteloostuijn et al, , 2021aVandermosten et al, 2019;West et al, 2019). Interestingly, a majority of the studies with children were administered to native speakers of Dutch van den Broeck, 2015, 2017;van der Kleij et al, 2018;Vandermosten et al, 2019;van Witteloostuijn et al, 2019van Witteloostuijn et al, , 2021a, of which all showed evidence of intact learning, except for performance on one of the tasks by Vandermosten et al (2019). Besides Dutch and English (Singh et al, 2018;West et al, 2019), tasks were also administered to native speakers in other languages, such as Cantonese (He and Tong, 2017;Tong et al, 2019), Hebrew (Schiff et al, 2017a), Portuguese (Inácio et al, 2018) and Swedish (Hedenius et al, 2020).…”
Section: Childrenmentioning
confidence: 99%
“…Continuing with this preliminary evaluation of studies listed in Table 1, certain task features tended to dominate over others. For example, there were more tasks pertaining to the visual and visual-motor domains versus the auditory-visual (Vandermosten et al, 2019) and auditory-motor (van Witteloostuijn et al, 2019(van Witteloostuijn et al, , 2021b. This modality issue is discussed further in Section "Discussion."…”
Section: Childrenmentioning
confidence: 99%
“…In the case of children with dyslexia, they performed significantly poorly in grammar because they tend not to focus on the morpho-syntactic features of the text [37]. A study by [38] reported that several studies [39,40] have shown that spoken language skills in young familial risks of dyslexia (FRdys) children produce shorter sentences of lower syntactic complexity and achieve lower vocabulary scores than low-risk children. In addition, when school-aged children with dyslexia or FRdys children are compared to their typically developing peers, they are found to achieve lower scores on standardized tests of grammar (e.g., the Clinical Evaluation of Language Fundamentals (CELF).…”
Section: Discussionmentioning
confidence: 99%
“…This has been proposed to help vocabulary learning [ 33 ]. Statistical learning ability has also been linked to phonological awareness [ 34 ], and it has been considered in relation to grammar skills [ 35 ].…”
Section: Is Statistical Learning Related To Reading?mentioning
confidence: 99%